CoS2/TiO2 Nanocomposites for Hydrogen Production under UV Irradiation - Sivagowri, S.; Velauthapillai, D.; Ravirajan, P.; Christy, A.A.; Shivatharsiny, Y. (Materials, 2019)
Transition metal chalcogenides have intensively focused on photocatalytic hydrogen production for a decade due to their stronger edge and the quantum confinement effect. This work mainly focuses on synthesis and hydrogen production efficiencies of cobalt disulfide (CoS2)-embedded TiO2 nanocomposites. Materials are synthesized by using a hydrothermal approach and the hydrogen production efficiencies of pristine CoS2, TiO2 nanoparticles and CoS2/TiO2 nanocomposites are compared under UV irradiation. A higher amount of hydrogen production (2.55 mmol g−1 ) is obtained with 10 wt.% CoS2/TiO2 nanocomposite than pristineTiO2 nanoparticles, whereas no hydrogen production was observed with pristine CoS2 nanoparticles. This result unveils that the metal dichalcogenide–CoS2 acts as an effective co-catalyst and nanocrystalline TiO2 serves as an active site by effectively separating the photogenerated electron–hole pair. This study lays down a new approach for developing transition metal dichalcogenide materials with significant bandgaps that can effectively harness solar energy for hydrogen production.
Keywords: Transition metal chalcogenides; Titania; Hydrothermal; Hydrogen; Water splitting